Is thyroid dysfunction a cause or a trigger of bipolar disorder? a case report - Yao, Jiashu; Xu, Jiating; Yan, Rong; Ye, Ruihuan; Shen, Yuedi; Dai, Ning; Chen, Wei (Frontiers in Psychiatry, 2024)
Here we report on a case of a 40-year-old female patient who presented with hypomanic episode after hyperthyroidism and major depressive episode after hypothyroidism, which was initially misdiagnosed as bipolar disorder due to another medical condition, and was found to be a co-morbid bipolar disorder of hyperthyroidism after treatment and follow-up. The course of diagnosis and treatment in this case suggests a close temporal relationship does not necessarily mean that there is a causal relationship on a physiologic level. User's Guide for the SCID-5-CV Structured Clinical Interview for DSM-5 Disorders elaborate that the diagnosis of "......due to another medical condition" is relatively rare, and co-morbidity between psychiatric disorders and somatic diseases is much more common. Therefore, the relationship between somatic diseases and psychiatric disorders requires careful study of symptom correlation and more time for observational follow-up. When in doubt, the examiner's default assumption should be that the somatic disease is not the cause (i.e., the psychiatric disorder is primary).